Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1055/s-2000-8587
|View full text |Cite
|
Sign up to set email alerts
|

Two New Acyclic Diterpene-γ-lactones from Salix matsudan

Abstract: Two new phytane-type diterpene-gamma-lactones named hanliuine I (1) and hanliuine II (2), were isolated from leaves of Salix matsudana (chinese name "hanliu", Berberidaceae). Their structures were deduced from 1D and 2D NMR techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…An acyclic diterpene-c-lactone, hanliuine I 154, has been obtained from Salix matsudan. 116 The lactone naviculide 155 has been obtained from the liverwort Porella navicularis, 117 whilst some geranyl-linalool glycosides, the capsiansides, have been reported from Capsicum plants. 118 The lactone 156 has been isolated from Melampodium leucanthum.…”
Section: Monofuranoditerpenoidsmentioning
confidence: 99%
“…An acyclic diterpene-c-lactone, hanliuine I 154, has been obtained from Salix matsudan. 116 The lactone naviculide 155 has been obtained from the liverwort Porella navicularis, 117 whilst some geranyl-linalool glycosides, the capsiansides, have been reported from Capsicum plants. 118 The lactone 156 has been isolated from Melampodium leucanthum.…”
Section: Monofuranoditerpenoidsmentioning
confidence: 99%
“…Salix denticulata which belongs to the Salicaceae family is a deciduous shrub indigenous to Central Himalayas (3000 meter) of India and is well known for its medicinal importance [1]. Previous studies on the plants of this genus led to isolation and elucidation of different compounds such as terpenoids [2], catechins [3], lignans [4], flavones [5,6] and other phenolic compounds [7]. This paper illustrates the isolation and structure revelation of a novel flavonoid glycoside (1) from the aereal parts of S. denticulata with the help of modern spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%
“…This species is occasionally used as a traditional medicine in India. The previous phytochemical research on Salix genus showed the presence of phenolics [4], condensed tannins [5], catechins [6], flavonols [7], and diterpenes [8]. As part of the research on medicinal plants of Garhwal Himalaya, we herein reported the isolation and characterization of a new flavonoid diglucoside along with four known flavonoids, luteolin [9], isoquercetin [10], catechin [11], and diosmetin [12], from the ethanolic extract of leaves of Salix denticulata.…”
mentioning
confidence: 98%